1986
DOI: 10.1128/jvi.57.3.992-997.1986
|View full text |Cite
|
Sign up to set email alerts
|

Demyelinating lesions due to Theiler's virus are associated with ongoing central nervous system infection

Abstract: We used in situ hybridization and immunocytochemistry to look for a correlation between virus expression and white matter lesions during late demyelinating disease due to persistent Theiler's virus infection. We found the following. (i) Tissue lesions developed at the site of virus infection. This correlation was not explained by infection of lymphocytes and macrophages. (ii) Large differences in the extent of pathology existed between mice. The amount of inflammation paralleled the number of cells containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…TMEV-induced demyelinating disease (TMEV-IDD) is a relevant model for human multiple sclerosis (MS) because many of the clinical symptoms and pathologic correlates are similar, including CD4 + T cell and mononuclear phagocyte infiltration into the CNS, primary demyelination and spastic hindlimb paralysis (Dal Canto and Lipton, 1975;Hafler, 2004;Lipton, 1975). In contrast, resistant mice are able to efficiently clear TMEV from the CNS and do not progress to demyelinating disease (Chamorro et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…TMEV-induced demyelinating disease (TMEV-IDD) is a relevant model for human multiple sclerosis (MS) because many of the clinical symptoms and pathologic correlates are similar, including CD4 + T cell and mononuclear phagocyte infiltration into the CNS, primary demyelination and spastic hindlimb paralysis (Dal Canto and Lipton, 1975;Hafler, 2004;Lipton, 1975). In contrast, resistant mice are able to efficiently clear TMEV from the CNS and do not progress to demyelinating disease (Chamorro et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In the second group, different viruses can infect glial cells and cause CNS demyelination. Among the RNA viruses, a mouse picornavirus causes demyelination during Theiler's murine encephalomyelitis (Aubert et al, 1987;Chamorro et al, 1986;Lipton and Dal Canto, 1976). In this model, virus persists at the sites of the lesions although at low levels, and infected cells appear to survive for prolonged periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Infected C57BL/6 mice do develop an acute disease, and have the ability to clear the virus. These mice do not go on to develop the late disease (Lipton & Dal Canto, 1979; Chamorro et al., 1986; Lindsley & Rodriguez, 1989; Pena‐Rossi et al., 1991). We previously reported that more than 50% of C57BL/6 mice infected with TMEV develop acute seizures between days 3 and 10 p.i.…”
mentioning
confidence: 99%